THE AGRICULTURAL PRODUCTS - MARKET STRUCTURE IN SOUTH-EAST EUROPE - Trivan, Dragan; Bakreski, Oliver; Bojić, Marko; Vukasović, Dragan; Stanojević, Miloš (Economics of Agriculture, 2018)
Purpose. The research subject is the analysis of exporting performance and international competitiveness of the Industry of agricultural products of SEE countries. Research goal is to examine the trends of total export effect, i.e. competitiveness effect (CE) trend, product effect (PE), geographical effect (GE) and residual effect (RE), as well as their components. Methodology. Constant market share (CMS) approach is able to explain these effects in the case of the Industry of agricultural products in SEE countries. Results. The conducted research covered 14 major products obtained from UN Comtrade, separated at four HTS code levels, in the period from 2007 to 2015. Conclusions. However, improvement of exporting competitiveness was still insufficient, considering that there was a more significant loss on other markets (EU, Russia).